The nature and extent of upper limb associated reactions during walking in people with acquired brain injury - Kahn, Michelle B.; Clark, Ross A.; Williams, Gavin; Bower, Kelly J.; Banky, Megan; Olver, John; Mentiplay, Benjamin F. (Journal of NeuroEngineering and Rehabilitation, 2019)
Upper limb associated reactions (ARs) are common in people with acquired brain injury (ABI). Despite this, there is no gold-standard outcome measure and no kinematic description of this movement disorder. The aim of this study was to determine the upper limb kinematic variables most frequently affected by ARs in people with ABI compared with a healthy cohort at matched walking speed intention.